Exploring the evocative qualities of masks’ visual imagery and their associations with adversity and trauma - Arslanbek, Asli; Malhotra, Bani; Stickley, Kristyn S.; Herres, Joanna; Spooner, Heather; Lamb, Damon G.; Levy, Charles E.; Williamson, John B.; Kaimal, Girija (Frontiers in Psychology, 2024)
Studies suggest a relationship between the emotional evocativeness of visual imagery and viewer responses, however, there is limited understanding of these associations, especially as they relate to viewers' personal experiences of adversities. In this exploratory study, we examined the relationship between the visual content of mask images and viewers' responses. In an online survey 699 participants (of n=1010 total initial participants) rated 98 masks based on valence, arousal, and personal relevance and completed the Life Events Checklist. The masks included those created by service members (SMs) with traumatic brain injury (TBI), and post-traumatic stress disorder (PTSD), depicting physical, psychological, and moral injuries and matched neutral masks created by creative arts therapists and arts in health scholars. The findings indicated that responses to mask image content (traumatic versus neutral) were associated with viewers' personal history of adversity and trauma. Specifically, images representing injury/ trauma provoked stronger reactions on valence and arousal than neutral images. Moreover, participants with personal histories of trauma had heightened emotional responses to distressing imagery. These findings have implications for art therapists as well as for clinical and general populations in that these results highlight the potential impact of distressing imagery particularly for individuals with personal histories of experiencing or witnessing traumatic events.